Informal Payments and Doctor Engagement in an Online Health Community: An Empirical Investigation Using Generalized Synthetic Control - Wang, Qili; Qiu, Liangfei; Xu, Wei (Information Systems Research, 2024)
Recognizing the importance of doctor engagement in online health communities (OHCs), managers and platform owners seek to foster doctor-patient interactions and encourage doctors’ knowledge sharing by introducing informal payments. This study investigates how informal payments in the form of monetary gifts affect doctor engagement, using the launch of a gifting feature by a leading OHC as a natural experiment that exogenously provides doctors with extra monetary incentives. We find that informal payments can have a crowding-out effect on doctors’ intrinsic motivation to engage in medical consultations. We also find that monetary and nonmonetary gifts play distinct roles in motivating doctor responses, with nonmonetary gifts having a more significant carryover effect on follow-up interactions and better promoting the doctor-patient relationship. Our findings additionally suggest that social status moderates the impact of digital gifting on doctor engagement. These findings provide useful implications for online health communities that have implemented or are planning to implement digital gifting to stimulate user engagement.